RENDEMEN, LIMBAH DAN KETEBALAN KULIT KAYU GALAM (Melaleuca leucadendron) DI INDUSTRI KECAMATAN LIANG ANGGANG KOTA BANJARBARU - Muhammad Dian Ilmi; Zainal Abidin; Noor Mirad Sari (Jurnal Sylva Scienteae, 2022)
The purpose of this study was to determine the percentage yield and industrial waste of barking galam (Melaleuca leucadendron) in Liang Anggang District, Banjarbaru City, South Kalimantan and correlation between the thickness of galam skin and the yield of galam wood in the skinning process. The results showed that the value of the percentage of natural yield obtained by the smallest average in the Riski trading unit was 73.63%. The largest percentage of yield value was found in the Sapri trading unit of 77.71%. The smallest waste was obtained in the Sapri trading unit of 22.29%, followed by the Hj trading unit. Ainah (23.76%), and the trading unit Riski (26.37%). The relationship or correlation between galam shell thickness (variable X) and yield (variable Y) resulted in an influential relationship between yield and thickness of galam shell. Galam bark affects the yield as much as 80% in each trading unit. Tujuan penelitian ini ialah untuk mengetahui persentase rendemen dan limbah industri pengulitan kayu galam (Melaleuca leucadendron) di Kecamatan Liang Anggang Kota Banjarbaru Kalimantan Selatan dan hubungan/korelasi antara ketebalan kulit galam dengan rendemen kayu galam dalam proses pengulitan. Hasil penelitian menunjukan bahwa Nilai persentasi rendemen galam didapatkan rata-rata terkecil pada unit dagang Riski sebesar 73,63%. Persentasi nilai rendemen terbesar didapatkan pada unit dagang Sapri sebesar 77,71%. Limbah terkecil didapat pada unit dagang Sapri sebesar 22,29% yang diikuti unit dagang Hj. Ainah (23,76%), dan unit dagang Riski (26,37%). Hubungan atau korelasi antara ketebalan kulit galam (Variabel X) dan rendemen (variabel Y) meghasilkan hubungan yang bepengaruh antara rendemen dan ketebalan kulit galam. Kulit kayu galam mempengaruhi rendemen sebanyak 80% disetiap unit dagang.